An Analysis of Category Shift in Me Before You Novel by Jojo Moyes - Pubas, Mutiarani; H. Hilman , Evert (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2022)
This research used a qualitative approach with descriptive design in order to find the translation shifting utilized by the translator from English to Indonesia and the translation quality assessment. The data were taken from the novel entitled Me Before You written by Jojo Moyes (2012) and from Indonesian-translated novel by Tanti Lesmana published in 2013. Furthermore, this research used Catford’s theory and Nababan et al., with the other theories, to find out the answer in the analyzing process. Catford divided translation shift into two, level shift and category shift. There are four types of category shift; structure shift, class shift, unit shift, and intra-system shift. The result showed that there were category shift that found in the data, which consist 28 unit shifts (57%), 12 intra-system shifts (23%) and 10 class shifts (20%). Translation quality assessment in three data shows less accuracy level dan the overall data indicates high accuracy level, high acceptability level, dan high readability level. As the implication, the result of this research has provided several new insights regarding the category shift in a written work which can be such a reference for other researchers in doing the similar focus of research.